2011
DOI: 10.1039/c1ob06150j
|View full text |Cite
|
Sign up to set email alerts
|

Protolimonoids and norlimonoids from the stem bark of Toona ciliata var. pubescens

Abstract: Six new tirucallane protolimonoids, toonapubesins A-F (1-6), one new rearranged tirucallane protolimonoid, toonapubesin G (7), and two new 21,22,23-trinorapotirucallane limonoids, toonapubesic acids A (8) and B (9), possessing an unprecedented carbon skeleton, along with five known tirucallane protolimonoids (10-14) and one known apotirucallane limonoid (15), were isolated from the stem bark of Toona ciliata var. pubescens. Their structures and relative configurations were determined by detailed spectroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…In contrast to our data, the limonoids isolated from Toona ciliata var. pubescens [16] were inactive or had weak activity on cancer and non-cancer cell line, but were able to inhibit CDC25B dual specificity phosphatase. Altogether, these data suggest a range of biological activity associated with a variety of limonoids molecules structures.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our data, the limonoids isolated from Toona ciliata var. pubescens [16] were inactive or had weak activity on cancer and non-cancer cell line, but were able to inhibit CDC25B dual specificity phosphatase. Altogether, these data suggest a range of biological activity associated with a variety of limonoids molecules structures.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29] However, the bioactive compounds responsible for antitumor remained elusive. Since cytotoxic activities of tirucallane-type triterpenoids had been reported, 15,30) we further examined the cytotoxic activities of compounds 1-9 using three human cancer cell lines by MTT assay. As shown in Table 3 Additionally, it was found that, compounds 1 and 2 showed the higher activities against MCF-7 and HepG-2 cell lines than compounds 3-7, indicating that the presence of the α,β-unsaturated ketone moiety at C-6, C-7 and C-8 might play an important role in the cytotoxicities.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the lower agglomeration provides more available surface area for interaction with bacterial membranes and for solubilisation of copper ions, which leads to more toxicity. Metallic and ionic forms of copper produce hydroxyl radicals that damage essential proteins and DNA [17]. Copper dissolves on surface of the bacteria and penetrate to the bacteria cells thereby breaking cell membrane.…”
Section: Flow Testmentioning
confidence: 99%